Patients' attitudes to risk in lung cancer surgery: A qualitative study. Issue 2 (November 2015) - Powell, HA; Jones, LL; Baldwin, DR; Duffy, JP; Hubbard, RB; Tod, AM; Tata, LJ; Solomon, J; Bains, M
Highlights: Patients were willing to accept high levels of perioperative mortality risk. Decisions seemed to be separate from understanding of risk estimates. Many indicated a preference for clinicians to make the treatment decision for them. There was desire to 'get rid of cancer' and perception of no alternative to surgery. Patients did not believe that adverse outcomes would happen to them. Abstract: Objectives: Lung cancer surgery leads to long term survival for some patients but little is known about how patients decide whether to accept the associated surgical risks. The objective of this qualitative study was to explore patients' attitudes to the risks associated with lung cancer surgery. Methods: Fifteen patients with resectable lung cancer, recruited via multi-disciplinary team meetings at an English tertiary referral centre, participated in semi-structured interviews to explore their attitudes to the morbidity and mortality risks associated with lung cancer surgery. Transcripts were analysed using the framework method. Results: Participants reported being ' pleased' to hear that they were suitable for surgery and felt that surgery was not a treatment to be turned down because they did not see any alternatives. Participants had some knowledge of perioperative risks, including mortality estimates; however, many voiced a preference not to know these risks and to let the medical team decide their treatment plan. Some found it difficult to relate the potential risks and complications of surgery to their own situation and appeared willing to accept high perioperative mortality risks. Generally, participants were willing to accept quite severe long-term postoperative breathlessness; however, it was apparent that many actually found this possibility difficult to imagine. Conclusion: Patients do not necessarily wish to know details of risks associated with lung cancer surgery and may wish to defer decisions about treatment to their medical team. Investment in the doctor–patient relationship, particularly for the surgeon, is therefore important in the management of patients with lung cancer.